TREATMENT OF BREAST CANCER; REVIEW AND UPDATES - Furrukh, Muhammad; Qureshi, Asim (Journal of Ayub Medical College Abbottabad, 2018)
Cancer of the breast is the leading female cancer accounting for one fourth of the malignancies. The tumour remains the most researched, read and practiced upon around the Globe. The treatment has substantially improved breast cancer related outcomes, both for early as well as late stages with substantial improvements in disease free and overall survival. Therapeutic decisions not only rest on clinical & tumour characteristics, but also with the evolution of molecular biology and tissue microarray intrinsic sub-types have been found. Attempts are being made to translate therapy from genomic architecture of individual breast cancer. This facilitates customization of treatment avoiding un-necessary toxicity, costs and inconvenience. Optimizing treatment based on individual breast biology seems logical and allows unifying treatment. The paper reviews literature, incorporate updates and also describes immunohistochemistry based molecular classification: which are found simple to adapt, record, present and subsequently manage, summarizing clinical practices in management of these patients. Keywords: Breast; Cancer; Molecular biology; Triple negative; Immunohistochemistry; Receptor, erb-B2;Therapy; Antibodies, Monoclonal